A Genome Wide Association Study Revealed Key Single Nucleotide Polymorphisms/Genes Associated With Seed Germination in Gossypium hirsutum L. - Si, Aijun; Sun, Zhengwen; Li, Zhikun; Chen, Bin; Gu, Qishen; Zhang, Yan; Wu, Liqiang; Zhang, Guiyin; Wang, Xingfen; Ma, Zhiying (Frontiers in Plant Science, 2022)
Fast and uniform seed germination is essential to stabilize crop yields in agricultural production. It is important to understand the genetic basis of seed germination for improving the vigor of crop seeds. However, little is known about the genetic basis of seed vigor in cotton. In this study, we evaluated four seed germination-related traits from a core collection consisting of 419 cotton accessions, and perform a genome wide association study (GWAS) to explore the important loci associated with seed vigor using 3.66 million high-quality single nucleotide polymorphisms (SNPs). The results showed that four traits, including germination potential, germination rate, germination index and vigor index, exhibited broad variations and high correlations. A total of 92 significantly associated SNPs located within or near 723 genes were identified for the traits, of which 13 SNPs could be detected in multiple traits. Among these candidate genes, 294 genes were expressed at seed germination stage. Further function validation of Gh_A11G0176 and Gh_A09G1509 showed that Gh_A11G0176 encoding Hsp70-Hsp90 organizing protein negatively regulated Arabidopsis seed germination, while Gh_A09G1509 encoding glutathione transferase played a positive role in regulating tobacco seed germination and seedling growth. Furthermore, Gh_A09G1509 might promote seed germination and seedling establishment through regulating glutathione metabolism in the imbibitional seeds. Our findings provide valuable information for understanding the genetic basis of seed germination and performing molecular breeding in improving cotton adaptive traits.